Práticas corporais de aventura na natureza: possibilidades de vivências e conscientização ambiental na escola e na cidade de Pirenópolis-GO - Teixeira, Bruna Brandão (2023)
This research addressed the possibilities of experiencing Body Practices of Adventure in Nature (PCAN) from the perspective of Environmental Education in school Physical Education classes and in the city of Pirenópolis-GO. During this research, we sought to promote a dialogue between Physical Education, Body Practices of Adventure in Nature and Environmental Education, in order to build a proposal for a didactic unit on PCAN that can be experienced at school and in the municipality. of Pirenópolis-GO, and also prepare a booklet on environmental awareness inside and outside adventure practices. The research problems came from questions such as: What is the learning through experience within the scope of Nature Adventure Body Practices inside and outside of school? Do Nature Adventure Body Practices contribute to students’ environmental awareness? The general objective of this study reflected on the limits and possibilities of a didactic unit on Body Practices of Adventure in Nature developed in Physical Education classes of the Final Years of Elementary School class at a State College in agreement with the Military Police of the city of Pirenópolis- GO, analyzing the bodily experiences induced through this theme and their possible contributions to students' environmental awareness. This is qualitative, descriptive research, classified based on the technical procedures used as critical action research. The research was composed of four classes from the 9th year of Elementary School, and only one of these classes was able to participate in the extracurricular class. The literature review sought, through different sources (books, articles published in specialized journals in the areas, laws, guidelines, parameters and curricular bases) to understand issues relating to Body Practices of Adventure in Nature, these and school Physical Education and Environmental Education. To produce the data, fifteen classes (theoretical and practical) were developed on the content of Body Practices for Adventure in Nature, focusing on Slackline, Orientation and Trekking. The Sequential Learning methodology, organized by Joseph Cornell (2008), was used in the development of the teaching unit, which has four phases that flow from one to the other (awakening enthusiasm, focusing attention, direct experience and sharing inspiration). Class analyzes were carried out using a semi-open questionnaire, notes from the field diary, photographic records and through a activities and research guided in the classroom that aimed to evaluate students' learning, perceptions and possible changes in conceptions regarding the topics covered, in addition to serving as support for the preparation of the Environmental Education booklet. The results of this study point to the importance of Physical Education as a discipline with great potential in the area of languages, capable of contributing effectively to students' environmental awareness through Body Practices of Adventure in Nature, enabling learning situations that provide changes in attitudes that help to modify their relationship with nature from the perspective of Environmental Education, enhancing the development of a certain degree of environmental awareness.